The effects of intensities, lighting periods of red led and blue led on growth, development on in vitro chrysanthemum (Chrysanthemum morifolium Ramat. CV. “Jimba”) - Tùng, Hoàng Thanh; Sang, Nguyễn Thanh; Tuấn, Nguyễn Xuân; Nam, Nguyễn Bá; Huy, Nguyễn Phúc; Hiền, Vũ Thị; Luận, Vũ Quốc; Nhựt, Dương Tấn (Vietnam Journal of Biotechnology, 2016)
In this study, the influence of different LED lighting intensities, different lighting periods of red LED and blue LED on growth, development and chlorophyll a and b synthesis on in vitro Chrysanthemum were presented. Shoot tips were inoculated and were put under 70% red LED: 30% blue LED lighting condition with different LED lighting intensities: 30, 45 and 60 µmol.m-2.s-1; different LED lighting periods: weekly intermittent lighting with red LED/blue LED (blue LED or red LED lighting for the first week), intermittent lighting with red LED/blue LED for each two weeks (blue LED or red LED lighting for the first two weeks). After 6 weeks of cultured, the results showed that LED lighting source with intensity 60 µmol.m-2.s-1 had the best stimulation on growth and development of Chrysanthemum; however, under intensity 45 µmol.m-2.s-1, chlorophyll a and b content still were the highest. In addition, weekly intermittent lighting with red LED and blue LED (blue LED was lighted at the first week) gave the best results on growth and development of Chrysanthemum. Thus, the most suitable LED lighting intensity for growth and development of in vitro Chrysanthemum was 60 µmol.m-2.s-1, and weekly intermittent lighting with red LED and blue LED (blue LED was lighted at the first week) will promote the growth and development of in vitro Chrysanthemum. The survival rates, growth and development of plants under 70% red LED: 30% blue LED and 50% red LED: 50% blue LED were higher than those of plants under Florescent, after 4 weeks of cultured in the greenhouse